Kuei Tung is the Panvesco President Because he's 'Pan Friendly' - Unknown (Newsday)
Former Finance Minister Brian Kuei Tung is the new chairman of Pan Trinbago’s Pan Investment Company (PANVESCO).
Keywords: Pan Trinbago (Organization); Steel bands (Music) -- Administration -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Kuei Tung, Brian